The Idea of Anthropological Key in the Sociotechnical Landscape Concept - Vladimir BUDANOV; Vladimir ARSHINOV; Irina ASEEVA (Communications of International Proceedings, 2020)
The new super-sophisticated technological pattern forming at the beginning of the 21st century demands its interpretation from the human and society point of view. The purpose of this interpretation is the search of adequate ways of human and new technical environment synergy. It is necessary to create new instruments of representation, monitoring and managing the complex phenomena of social techno sphere in order to explicate these processes. We are continuing to study this topic through constructionist development of sociotechnical landscape (STL) concept, the formation of anthropological keys of its understanding and interpretation. The methods of synergy, quantum theory and quantum synergy anthropology are used to search of the instruments and work with STL, create local landscapes based on different taxons in the conditions of complex topology and create anthropological keys in order to find out the basic characteristics of evaluating STL.
Keywords: Sociotechnical Landscape; Digitalization; Anthropological Key; Generalized Embodiment; Anthropological Profile.